Pandemic Economics and the Transformation of Health Policy - Xi Chen; Annie Fan (Institute of Labor Economics (IZA), 2021)
The Coronavirus Disease 2019 (COVID-19) pandemic is bringing about once-in-a-century changes to human society. This article summarizes key characteristics of the COVID-19 pandemic that should be incorporated in economics and health policy analyses. We then review the literature on the importance of public health measures, including taking early, targeted, and coordinated actions, enhancing social safety nets for vulnerable populations, and strengthening public communications. In the long term, addressing misallocation of health resources and improving health governance are critical. Drawing on evidence from past and present epidemics as well as comparing cross-country variations in their responses to the current public health emergency, we navigate long-awaited health reforms in areas that help optimize epidemics response and realign incentives of the major players in the health sector in preparation for the next pandemic.
Keywords: I18; J24; H12; P41; H51; 330; COVID-19; pandemic; healthcare reform; health governance; global health policy